Activation of Transient Receptor Potential Vanilloid 4 Increases NMDA-Activated Current in Hippocampal Pyramidal Neurons - Li, Lin; Qu, Weijun; Zhou, Libin; Lu, Zihong; Jie, Penghui; Chen, Lei; Chen, Ling (Frontiers in Cellular Neuroscience, 2013)
The glutamate excitotoxicity, mediated through N-methyl-D-aspartate receptors (NMDARs), plays an important role in cerebral ischemia injury. Transient receptor potential vanilloid 4 (TRPV4) can be activated by multiple stimuli that may happen during stroke. The present study evaluated the effect of TRPV4 activation on NMDA-activated current (INMDA) and that of blocking TRPV4 on brain injury after focal cerebral ischemia in mice. We herein report that activation of TRPV4 by 4α-PDD and hypotonic stimulation increased INMDA in hippocampal CA1 pyramidal neurons, which was sensitive to TRPV4 antagonist HC-067047 and NMDAR antagonist AP-5, indicating that TRPV4 activation potentiates NMDAR response. In addition, the increase in INMDA by hypotonicity was sensitive to the antagonist of NMDAR NR2B subunit, but not of NR2A subunit. Furthermore, antagonists of calcium/calmodulin-dependent protein kinase II (CaMKII) significantly attenuated hypotonicity-induced increase in INMDA, while antagonists of protein kinase C or casein kinase II had no such effect, indicating that phosphorylation of NR2B subunit by CaMKII is responsible for TRPV4-potentiated NMDAR response. Finally, we found that intracerebroventricular injection of HC-067047 after 60-min middle cerebral artery occlusion reduced the cerebral infarction with at least a 12-h efficacious time-window. These findings indicate that activation of TRPV4 increases NMDAR function, which may facilitate glutamate excitotoxicity. Closing TRPV4 may exert potent neuroprotection against cerebral ischemia injury through many mechanisms at least including the prevention of NMDAR-mediated glutamate excitotoxity.